Proportion and Factors that Associate with Incidence of Hepatotoxicity in Rheumatoid Arthritis Patients Treated with Methotrexate in RSCM Year 2013â2015 - Prathitasari, Rahma Anindya; Isbagio, Harry (Indonesian Rheumatology Association, 2018)
Background Rheumatoid arhtirtis (RA) is a chronic autoimmune disease that mainly attacks joints. It may causes joint deformities which leads to lower quality of life of RA patients. RA is treated with metothrexate (MTX) which inhibiting disease progression. MTX is known for its hepatotoxicity side effect, which is described by an elevation of aspartate aminotransferaseÂ (AST) and/or alanine aminotransferase (ALT) beyond the upper normal limit. Factors that may enhance hepatotoxicity are gender, age, cummulative dose of MTX, and duration therapy of MTX. Prevalence of hepatotoxicity caused by MTX therapy in RA patients in Indonesia is still unknown. The objective of this research is to know the proportion of hepatotoxicity and its associations with the factors that may enhance hepatotoxicity caused by MTX therapy in RA patients in RSCM.Method Data about gender, age, cummulative dose and duration therapy of MTX are obtained from 115 RA patients medical records.Result Proportion of hepatotoxicity in RA patients treated with MTX in RSCM is 42.60%. Gender, age, cummulative dose and duration therapy of MTX do not significantly enhance hepatotoxicity (p>0.05).Conclusion In conclusion gender, age, cummulative dose and duration therapy of MTX do not have association with hepatotoxicity in RA patients treated with MTX.Â Keywords: Rheumatoid Arthritis, Methotrexate, Hepatotoxicity